The Aramaic Inscriptions of Sefire - Fitzmyer, Joseph A. (1967)
Stelae I-III. The Affinity of the Sefire Inscriptions to Hittite and Assyrian Treaties. The Land of KTK. Appendix: The Grammar of the Sefire Inscriptions. Glossary. Proper Names in the Text.